Organic- and carbonate-carbon values and extract data for DSDP Holes 63-467 and 63-471 - Jürgen Rullkötter; Hans von der Dick; Dietrich Hugo Welte (PANGAEA, 1981)
Quantity, type, and maturity of the organic matter of middle Miocene to Quaternary sediments from the eastern North Pacific (Deep Sea Drilling Project Leg 63) were determined. Hydrocarbons and fatty acids in lipid extracts were analyzed by capillary column gas chromatography and combined gas chromatography/mass spectrometry. Kerogens were investigated by Rock-Eval pyrolysis and microscopy, and vitrinite reflectance values were determined. At Site 467, in the San Miguel Gap of the outer California Continental Borderland, organic carbon contents range from 1.46% to 5.40%. Normalized to organic carbon, total extracts increase from about 10 to 36 mg/g Corg with depth. The organic matter is a mixture of both marine and terrestrial origin, with the marine organic matter representing a high proportion in some of the samples. Steroid hydrocarbons - sterenes and steradienes in the upper part of the section and steranes in the deepest sample - are the most abundant compounds in the nonaromatic hydrocarbon fractions. Perylene, alkylated thiophenes, and aromatic steroid hydrocarbons dominate in the aromatic hydrocarbon fractions of the shallower samples; increasing maturation is indicated by a more petroleumlike aromatic hydrocarbon distribution. Microscopy revealed a high amount of liptinitic organic matter and confirmed the maturation trend as observed from analysis of the extracts. The vitrinite reflectance may be extrapolated to a bottom-hole value of nearly 0.5% Ro. The liquid hydrocarbon potential of the sediments at higher maturity levels is rated to be good to excellent. At Site 471, off Baja California, organic carbon values are between 0.70% and 1.12%. Extract values increase with depth, as at Site 467. The investigation of the soluble and insoluble organic matter, despite some compositional similarities, consistently revealed a more terrigenous influx compared with Site 467. Thus the potential for liquid hydrocarbon generation is lower, the organic matter being more gas-prone. The deepest sample analyzed indicates the onset of hydrocarbon generation. At this site, frequent sand intercalations offer pathways for migration and possibly reservoir formation.
Supplement to: Rullkötter, J et al. (1981): Organic petrography and extractable hydrocarbons of sediments from the eastern North Pacific Ocean, Deep Sea Drilling Project Leg 63. In: Yeats, RS; Haq, BU; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 63, 819-836, https://doi.org/10.2973/dsdp.proc.63.134.1981